2012
DOI: 10.1007/s10903-012-9581-y
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner and Client Explanations for Disparities in Health Care Use Between Migrant and Non-migrant Groups in Sweden: A Qualitative Study

Abstract: To investigate variations in explanations given for disparities in health care use between migrant and non-migrant groups, by clients and care providers in Sweden. Qualitative evidence collected during in-depth interviews with five 'migrant' health service clients and five physicians. The interview data generated three categories which were perceived by respondents to produce ethnic differences in health service use: "Communication issues", "Cultural differences in approaches to medical consultations" and "Eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 9 publications
5
39
0
Order By: Relevance
“…In agreement with previous studies [42, 43], HCPs in this study indicated that refugee and migrant women are a diverse group in relation to their migration history and experience, age, education, culture, socio-economic background, country of origin experience in accessing health care, length of stay in Australia and SRH knowledge. However, common concerns around accessing and utilising the available SRH information and services and SRH literacy were indicated in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies [42, 43], HCPs in this study indicated that refugee and migrant women are a diverse group in relation to their migration history and experience, age, education, culture, socio-economic background, country of origin experience in accessing health care, length of stay in Australia and SRH knowledge. However, common concerns around accessing and utilising the available SRH information and services and SRH literacy were indicated in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Of importance, however, patients also blame themselves for their lack of knowledge rather than recognize that providers may improve communication to better inform patients of their choices and care processes. Such attitudes may create power disparities between providers and migrants that lead to abuse of patients [36]. In Ghana, a study of differential treatment between the “educated elite” and non-elite “villager” in healthcare settings hypothesizes that these differences are tied to larger social inclusion and exclusion of those who are educated versus non-educated in Ghanaian society at large [14].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the literature suggests that this continuous growth of foreign born populations with varied cultural traits and health profiles, presents complex challenges for health care delivery due to change in disease profiles, communication problems, diversity of cultures and institutional practices as well as individual past experiences and attributes [6-14]. These challenges are said to influence medical encounters and can result in mistrust that may lead to sub-optimal utilization of health services, frustrations and calamitous errors in diagnosis and treatment regimens [7-10,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…These challenges are said to influence medical encounters and can result in mistrust that may lead to sub-optimal utilization of health services, frustrations and calamitous errors in diagnosis and treatment regimens [7-10,15,16]. Literature on cross-cultural health care indicates that migrant populations present unique challenges to health professionals, and can be a source of frustration for health professionals as they may struggle with uncertainty and apprehension when caring for these patients [6-13,15,17,18]. Previous studies suggest that caring for patients who speak a different language is difficult because of lack of or unavailability of interpreters or problems in accessing interpreter agencies, which in some cases force care providers to use family members as interpreters.…”
Section: Introductionmentioning
confidence: 99%